Corporate finance : theory and practice / Pierre Vernimmen ; Pascal Quiry ... [et al.]. - Vernimmen, Pierre.
Đầu trang nhan đề:Adapted and updated from the original French, first published as "Finance d'entreprise" by Éditions Dalloz, Paris, 1994